Implementation of Multimedia Development Life Cycle in Short Film Production: A Case Study of “Bipol in Love” - Yoseph Satria Praka; Rifqy Arifin Atthalah; Sonia Juni Arta Simare Mare; Bramantya Destalenta; Mira Rosalina (Jurnal Ilmiah Multimedia dan Komunikasi, 2026)
The development of multimedia technology has encouraged the increasing use of short films as an effective medium for delivering information, entertainment, and social messages. This study aims to analyze the implementation of the Multimedia Development Life Cycle (MDLC) method in the production process of the short film “Bipol in Love.” The film tells the story of student life and romance inspired by the Bus Poltek transportation facility at Politeknik Negeri Jakarta. This research applied a qualitative creation-based approach using six MDLC stages: concept, design, material collecting, assembly, testing, and distribution. The concept stage determined the film objectives, target audience, and storyline, while the design stage focused on scriptwriting and storyboard creation. Material collecting involved filming and gathering multimedia assets from several locations, followed by the assembly stage using multimedia editing software to produce the final video. The testing stage was conducted through internal alpha testing to evaluate the quality of the film. The results showed that the MDLC method supported the production process of the short film “Bipol in Love” systematically and efficiently. The final output was a 16-minute and 12-second short film distributed through YouTube and promoted via Instagram. Therefore, the study concludes that the MDLC method was effective in organizing and managing the production activities of the short film “Bipol in Love.”